PENGARUH SKEPTISME AUDIT, INDEPENDENSI DAN KOMPLEKSITAS TUGAS TERHADAP AUDIT JUDGMENT - Parhan, Ian; Kurnia, Kurnia (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
An audit judgment is a decision which is issued by an auditor based on doucmentation of evidences which have been found. The purpose of this research is to examine the influence of audit scepticism, independency, and task complexity to the audit judgment. The respondents in this research are auditors (managers, partners, senior auditors and junior auditor) who have been working on Public Accounting Firms in Surabaya. The sample collection has been carried out by using purposive sampling method in which it is a sample selection method which is based on certain criteria. The data analyis technique has been carried out by using multiple linear regressions analysis. The result of the research shows that audit skepticism give positive influence to the audit judgment, this mean on the level of audit skepticism an auditor in conducting the audit, his judgment is give better, and task complexity give positive influence to the audit judgment, this mean auditor feels the audit task his faces a complex task, so the auditor has difficulty in performing the task and canât make professional judgment; Meanwhile, independency does not give any influence to the audit judgment, this mean low the auditor independence level, then low quality result audit judgment produce.Keywords: Audit scepticism, independency, task complexity, audit judgment